Is it time to reconsider the incremental test protocols? - Cortis, C.; Fusco, A.; Barroso, R.; Bok, D.; Boullosa, D.; Conte, D.; Foster, C. (International Journal of Sports Physiology and Performance, 2023)
In recent years, the editorials "Sport Science on Women, Women in Sport Science"1 and "Sport-Science Research on Female Athletes: Dealing With the Paradox of Concurrent Increases in Quantity and Quality"2 encouraged authors of the International Journal of Sport Physiology and Performance to increase research focusing on female athletes. The journal went from, in 2019, 19% of papers including female athletes1 to, in 2022, 28% including female athetes,2 while studies performed exclusively on women went from 4% to 12%. The papers including women or focusing exclusively on female athletes mainly dealt with performance and training. To set targeted training intensities, graded maximal or submaximal testing outcomes such as ventilatory threshold (VT) are used. Since physiological responses to exercise and testing differ between men and women, information on testing procedures to identify VT specifically tailored for female athletes could be helpful to optimize training strategies.